A normal contact stiffness model of machined joint surfaces considering elastic, elasto-plastic and plastic factors. (July 2020) - Zhang, Yongquan; Lu, Hong; Zhang, Xinbao; Ling, He; Fan, Wei; Bao, Liu; Guo, Zexing
Considering the rough surface as a fractal model makes the research of contact parameters more practical. In the fractal model of the machined surface, the parameters describing the surface topography are independent of the measurement resolution. Based on the elastic, elasto-plastic and plastic deformations of a single pair of contact asperities, a normal contact stiffness model using the fractal model for surface topography description is proposed in this paper. The specimens machined by milling and grinding methods are used to verify the proposed contact stiffness model based on the fractal theory. The experimental and theoretical results indicate that the proposed contact stiffness model is appropriate for the machined joint surfaces.